Pilot study of the productivity and Salmonella seroprevalence in pigs administered organic acids - Roldan-Henao, Manuela; Dalsgaard, Anders; Cardona-Castro, Nora; Restrepo-Rivera, Lina; Veloza-Angulo, Luis Carlos; Alban, Lis (Frontiers in Veterinary Science, 2023)
Control of Salmonella in pig/pork production is important to protect public health because pork is one of the main sources of human infection. Moreover, antimicrobial use in pig farms should be kept low to minimize development and transmission of antimicrobial resistance. This pilot study evaluated the productivity and Salmonella seroprevalence in pigs administered organic acids (OA) compared to pigs given growth promoters in one farm in Antioquia, Colombia. Two groups each consisting of 60 pigs of 6-weeks of age were studied for 4 months. One group was provided feed and water with OA (Selko pH® and Selacid®), whereas the other group (control) received antimicrobial growth promoters according to routine feeding practices (tylosin and zinc bacitracin). Blood samples were taken three times (T1–T3) and pigs were weighted five times to calculate daily weight gain (DWG) and feed conversion ratio (FCR). Initially when the pigs were 6 weeks old (T1), the Salmonella seroprevalence was 1.7% in both groups. When the pigs were 11 weeks old (T2), the seroprevalence was significantly lower in pigs provided OA compared to the control group (19 vs. 47%, P < 0.001), whereas when the pigs were 23 weeks old (T3), the seroprevalence did not differ between the groups (62 vs. 77%; P = 0.075). The cumulative DWG was significantly higher in the intervention group than in the control group (713 vs. 667 g/day; P < 0.001). The cumulative FCR did not differ between groups (2.80 vs. 2.77; P = 0.144). The pilot study indicates that cleaning the water pipes and administrating OA improve productivity in pigs and delay exposure to Salmonella spp. when compared with growth promoters. Thus, OA could replace antimicrobial growth promoters and reduce antimicrobial use and resistance. However, the study should be repeated before firmer conclusions can be drawn.